2019
DOI: 10.1002/aenm.201902726
|View full text |Cite|
|
Sign up to set email alerts
|

Progress of Surface Science Studies on ABX3‐Based Metal Halide Perovskite Solar Cells

Abstract: ABX3 type metal halide perovskite solar cells (PSCs) have shown efficiencies over 25%, rocketing toward their theoretical limit. To gain the full potential of PSCs relies on the understanding of the device working mechanisms and recombination, the material quality, and the match of energy levels in the device stacks. In this review, the importance of designing PSCs from the viewpoint of surface/interface science studies is presented. For this purpose, recent case studies are discussed to demonstrate how probin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 364 publications
0
67
0
Order By: Relevance
“…[ 2,18–27 ] However, it is still difficult to accurately identify defect types including Pb 2+ /halide vacancies, interstitial Pb 2+ /halides, and undercoordinated Pb 2+ /halides for these multicomponent perovskites. [ 11,28–30 ] Therefore, identifying defect types and adopting suitable passivators are crucial not only to boost the efficiency but also to slow down the moisture degradation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,18–27 ] However, it is still difficult to accurately identify defect types including Pb 2+ /halide vacancies, interstitial Pb 2+ /halides, and undercoordinated Pb 2+ /halides for these multicomponent perovskites. [ 11,28–30 ] Therefore, identifying defect types and adopting suitable passivators are crucial not only to boost the efficiency but also to slow down the moisture degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Hole mobility is lower than electron mobility. The performance of PSCs is governed by the balance of charge carrier generation, recombination processes, transport across the bulk, and extraction at the interfaces . The balanced mobility between hole and electron can effectively improve the performance of PSC.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of PSCs is governed by the balance of charge carrier generation, recombination processes, transport across the bulk, and extraction at the interfaces. [7] The balanced mobility between hole and electron can effectively improve the performance of PSC. Therefore, many efforts have focused on the hole transport layer (HTL)/perovskite interface regulation of PSCs to improve the PCE and stabilize PSCs.…”
mentioning
confidence: 99%
“…This is in agreement with results obtained through surface and grain boundaries passivation. [ 26,27 ] Recent theoretical studies have demonstrated a lower formation energy of defects on the surface. [ 28 ] By definition, the surface represents an extended defect, the simple discontinuity will modify the bonds geometry (i.e., lengths and angles) modifying the way carriers will couple to the lattice and their recombination rates as well as the thermodynamic ionization level of defects which will eventually interact with carriers.…”
Section: Defects In Perovskite Solar Cells: Efficiency Versus Stabilitymentioning
confidence: 99%